INNOVATION IN HUMAN RESOURCE DEVELOPMENT: CHALLENGES AND DETERMINING FACTORS - Hakiki, Ridwan; Adi Robith Setiana; Asep Saeful Falah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Innovation in human resource development (HRD) is a key factor in enhancing organizational competitiveness in the digital era. This study discusses various trends in HRD innovation, key success factors, implementation challenges, and recommendations to improve the effectiveness of these innovations. The findings indicate that the utilization of digital technology, flexibility in workforce management, data-driven talent management, and gamification in training are the main trends in HRD innovation. The success of these innovations is influenced by management support, an innovative organizational culture, the use of technology, and employee engagement. However, several challenges remain, including resistance to change, skill gaps, and budget constraints. Therefore, organizations need to increase investment in HR technology, adopt digital-based training models, build an adaptive organizational culture, and develop flexible career development programs. By implementing these strategies, HRD innovation can be more effective in supporting organizational growth and preparing the workforce for the ever-evolving industry dynamics. Keywords: HRD Innovation, Digital Technology, Talent Management, Employee Training, Career Development